(untitled) (Texas Journal of Medical Science, 2024)
This article explores the mental state of patients diagnosed with oncological diseases, examining the psychological impact of cancer diagnoses and treatments. It delves into literature analysis, methodologies for studying mental health in oncology patients, results of recent studies, and discussions on the implications for patient care. Recommendations for improving psychological support in oncological care settings are provided.